Ultrasound renal denervation in hypertensive patients: A systematic review and meta-analysis. - Roy Novri Ramadhan; Derren David Christian Homenta Rampengan; Felicia Angelica Gunawan; Nathania; Sebastian Emmanuel Willyanto; Hiroyuki Yamada; Mochammad Thaha; Satriyo Dwi Suryantoro; Maulana Antiyan Empitu (PLoS ONE)
Introduction Hypertension is the leading noncommunicable disease case affecting 1.28 billion individuals worldwide, with most cases located in low- and middle-income countries. While there are numerous techniques for treating mild to moderate hypertension, properly controlling severe or resistant hypertension poses substantial challenges. Ultrasound-based renal denervation (uRDN) has emerged as a promising non-pharmacological approach. This study aims to investigate the safety and efficacy of uRDN in hypertensive patients. Methods The literature search across PubMed, ScienceDirect, BMJ Journals, ProQuest, and Springer databases yielded 419 articles. A total of 395 articles were filtered, leading to 24 articles assessed for eligibility and overall analysis, which resulted in eight included studies for quantitative synthesis. Quality appraisal used RoB 2.0, while meta-analysis used RevMan 5.4. Results Our analysis results indicated significant improvements in 24-hour, daytime, and home ambulatory blood pressure measurements, favoring the uRDN over control. The mean difference (MD) for 24-hour measurements was -0.84 mmHg [95% CI -1.14, -0.55; p < 0.00001], for daytime measurements -1.27 mmHg [95% CI -1.59, -0.95; p < 0.00001], and for home measurements -1.98 mmHg [95% CI -2.32, -1.64; p < 0.00001], with moderate heterogeneity observed. Office ambulatory measurements also favored the uRDN with a significant MD of -1.51 mmHg [95% CI -1.91; -1.10; p < 0.00001]. Funnel plots revealed some outliers, indicating true heterogeneity among the studies. Conclusion uRDN was associated with a significant reduction (-2.32 to -0.10 mmHg) in blood pressure of hypertensive patients.